If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + -2 = -2(1 + 5r) Reorder the terms: -2 + 2r = -2(1 + 5r) -2 + 2r = (1 * -2 + 5r * -2) -2 + 2r = (-2 + -10r) Add '2' to each side of the equation. -2 + 2 + 2r = -2 + 2 + -10r Combine like terms: -2 + 2 = 0 0 + 2r = -2 + 2 + -10r 2r = -2 + 2 + -10r Combine like terms: -2 + 2 = 0 2r = 0 + -10r 2r = -10r Solving 2r = -10r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '10r' to each side of the equation. 2r + 10r = -10r + 10r Combine like terms: 2r + 10r = 12r 12r = -10r + 10r Combine like terms: -10r + 10r = 0 12r = 0 Divide each side by '12'. r = 0 Simplifying r = 0
| 3x+25=16 | | 64=w(2w+8) | | 60/d=12/122 | | 1/2x+5=-4/3(x+6) | | 62=w(2w+8) | | 62=w(2w+8) | | 200x-5600=-2800 | | 1/8x | | 4x+(x-2)=3 | | -5r+8(r-3)=6+8r | | 200x-5600=0 | | 14-2x=30 | | 6(2y+6)+(-33y)= | | 10n+12=4n-12 | | 2-6y+5=3y+13-6y | | 5-2p=13 | | (0.75x+6)-(2.5x-1.9)= | | 8(4x-7)=-88 | | 10x+10-9x=-8+6x-4 | | 12m=18 | | 4-2[-3]= | | 6y+4-9y-10= | | 3(0.9-the)=-5(16.5+3t) | | -8(5-7n)=-264 | | 7(b+4)=7b+32 | | 10(v+3)-2v=2(4v+4)-15 | | 2*x^2+4*x+2=0 | | 3a-53-a= | | 3(p+2)=-2(3p-3) | | -14+9(-2)= | | 64/x=8/21 | | 39+5a=2(-6a-6) |